2010
DOI: 10.1100/tsw.2010.87
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond Health to Flourishing: The Effects of Yoga Teacher Training

Abstract: Research in the medical and psychological fields has primarily followed a “disease-focused” approach to health. Although there is growing research on the components and outcomes of well-being, very few studies have focused on traditional practices that can be used as interventions to encourage human flourishing. The current study was developed to address this research gap. We suggest one effective method of increasing psychological well-being, the practice of yoga, an age-old practice that has been said to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 20 publications
3
22
1
2
Order By: Relevance
“…Our finding that participation in the SI program predicts an increase in mindfulness is consistent with some recent reports suggesting that yoga-based programs can also increase the skill of mindfulness (Conboy et al, 2010;Shelov et al, 2009). This increase in mindfulness might be attributed to the emphasis on the cultivation of 'witness consciousness' in the SI program.…”
Section: Mindfulnesssupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that participation in the SI program predicts an increase in mindfulness is consistent with some recent reports suggesting that yoga-based programs can also increase the skill of mindfulness (Conboy et al, 2010;Shelov et al, 2009). This increase in mindfulness might be attributed to the emphasis on the cultivation of 'witness consciousness' in the SI program.…”
Section: Mindfulnesssupporting
confidence: 91%
“…Although there is some preliminary evidence that yoga increases mindfulness (Conboy, Wilson, & Braun, 2010;Shelov, Suchday, & Friedberg, 2009), its role as a mediator of the effect of yoga on stress and well-being has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The interviews revealed two themes within body awareness: overt tuning into the body (kinesthetic sensitivity) and being kind to one's body (self-acceptance and self-compassion); improvements in self-compassion have been found to result from other Kripalu yoga programs, 34 suggesting that this may be a mechanism of change associated with yoga practice. Furthermore, despite lacking any reference to healthy eating behaviors in the present study's yoga curriculum, one interviewed student also reported changes in eating habits from participating in yoga classes.…”
Section: Discussionmentioning
confidence: 99%
“…Conboy et al [70] konnten eine Steigerung von Flourishing durch Yoga nachweisen, das zu den Mind-Body-medizinischen Anwendungen zählt. Es erscheint konzeptionell vorstellbar, dass Mind-Body-Anwendungen einen Einfluss auf die persönliche Entwicklung und das persönliche Wachstum (Selbsteinschätzung) haben können.…”
Section: Diskussionunclassified
“…Catalino und Fredrickson [71] wiesen nach, dass Veränderungen der Achtsamkeit mit Veränderungen des Flourishing einhergehen. Dies passt mit den Ergebnissen von Conboy et al zusammen [70]. Die Korrelation zwischen dem FS-D und dem SOC9 liegt ebenfalls im mittleren Bereich.…”
Section: Diskussionunclassified